“Words, Words, Words.—Between Who?”: Alterations and Interpolations in the RSC Chinese Translation of Hamlet - Cong, Cong (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
This article is a case study examining the Royal Shakespeare Company’s Chinese translation of Hamlet, which is part of its “Shakespeare Folio Translation Project” that was launched in 2015. Textual interpolations and alterations of the plot in this version are demonstrated, ranging from cuts of critical scenes and roles to lines and single words rendered in an “audience-friendly” way into an alleged Chinese context. Based on an analysis of the translator’s edits, textual transpositions, and choices of Chinese wording, this paper recognizes this version’s contribution to the diversity and acculturation of Shakespeare for a special intellectual community in a different culture in twenty-first-century China. Nevertheless, it proposes that this edition be more accurately entitled “RSC Hamlet for the Chinese Stage” rather than the officially designated “RSC Chinese Folio Hamlet” in order to avoid possible misconceptions of “acknowledged authority” that Chinese readers and audience may conceive under the halo of RSC and the misleading label of “Commissioned Folio Translation.”